Isolation and Characterization of the Eicosapentaenoic Acid Biosynthesis Gene Cluster from Shewanella sp. BR-2 - Lee, S.J., Molecular Bioprocess Research Center, Jeonbuk Branch Institute, KRIBB, Jeongeup, Republic of Korea; Seo, P.S., Molecular Bioprocess Research Center, Jeonbuk Branch Institute, KRIBB, Jeongeup, Republic of Korea; Kim, C.H., Molecular Bioprocess Research Center, Jeonbuk Branch Institute, KRIBB, Jeongeup, Republic of Korea; Kwon, O.S., Korea Research Institute of Bioscience and Biotechnology, Daejeon, Republic of Korea; Hur, B.K., Inha University, Incheon, Republic of Korea; Seo, J.W., Molecular Bioprocess Research Center, Jeonbuk Branch Institute, KRIBB, Jeongeup, Republic of Korea (Journal of microbiology and biotechnology, 2009)
Forty-four eicosapentaenoic acid (EPA)-producing microbial strains were isolated from the intestines of marine fishes. Among them, one strain showing a maximum level of EPA (4.78% of total fatty acids) was identified as Shewanella sp. BR-2 on the basis of its 16S rRNA sequence. The EPA content reached a maximum level during the mid-exponential phase of cell growth, and gradually decreased with further growth of the cells. A cosmid DNA including the EPA biosynthesis gene cluster consisting of pfaA-E was isolated from a cosmid library of genomic DNA of Shewanella sp. BR-2, named pCosEPA-BR2. An E. coli clone harboring pCosEPA-BR2 produced EPA at a maximum level of 7.5% of total fatty acids, confirming the EPA biosynthesis activity of the cloned gene cluster.